2016
DOI: 10.1186/s13567-016-0309-1
|View full text |Cite
|
Sign up to set email alerts
|

Barrier protection via Toll-like receptor 2 signaling in porcine intestinal epithelial cells damaged by deoxynivalnol

Abstract: Intestinal barrier is the first line of defense inside the body and comprises intercellular tight junction (TJ) proteins that regulate paracellular permeability. Deoxynivalenol (DON), a fungal metabolite often found in the contaminated food of domestic animals, is known to impair intestinal barrier function and may be involved in intestinal inflammation. Unlike in humans and mice, the importance of Toll-like receptor (TLR) 2 expressed in porcine intestinal epithelial cells is largely unclear. Therefore, the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 38 publications
0
35
2
Order By: Relevance
“…Regarding the influence of DON on TJ proteins of IPEC-J2, literature reports exist with respect to ZO-1, claudin-3 and occludin [ 10 , 45 , 82 , 83 ]. Gu et al [ 83 ] reported ZO-1 reductions after 72 h basolateral exposure to DON (6.73 µM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the influence of DON on TJ proteins of IPEC-J2, literature reports exist with respect to ZO-1, claudin-3 and occludin [ 10 , 45 , 82 , 83 ]. Gu et al [ 83 ] reported ZO-1 reductions after 72 h basolateral exposure to DON (6.73 µM).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the influence of DON on TJ proteins of IPEC-J2, literature reports exist with respect to ZO-1, claudin-3 and occludin [ 10 , 45 , 82 , 83 ]. Gu et al [ 83 ] reported ZO-1 reductions after 72 h basolateral exposure to DON (6.73 µM). Others demonstrated—in accordance with our finding—no [ 45 ] or only slight [ 10 , 82 ] DON-induced (6.73 µM) ZO-1 reductions in apically treated IPEC-J2, but strong effects in cells exposed basolaterally for 72 h. While our finding of a DON-induced claudin-3 decrease is in accordance with Gu et al [ 83 ], others report no effect of DON on claudin-3 in apically treated IPEC-J2 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4c). These effects could notably be explained by the ability of A. muciniphila to activate TLR2 via Amuc_1100, as this receptor can regulate various tight-junction proteins including Occludin and Claudin 3 31,32 . In the colon, untreated HFD-fed mice had a higher Ocln expression as compared to the other groups,…”
mentioning
confidence: 99%
“…Toll-like receptors 4 (TLR4) is a trans-membrane proteins, an important member of the toll-like receptors family, which detect the PRRs and activate the NF-κB (intracellular signaling pathway), which ultimately activate immune response by producing pro-inflammatory cytokines (Fig. 2) (Lebeer et al, 2010;Gu et al, 2016). Some studies exposed that IgA is the dominant immunoglobulin in the intestine and plays a key role in immunity (Mahfuz et al, 2017).…”
Section: Associated Immune Responsesmentioning
confidence: 99%